Alternative energy sources: opportunities, experience and prospects of the Russian regions in the context of global trends - Samarina, Vera; Skufina, Tatiana; Samarin, Ðlexander; Ushakov, Denis (International Journal of Energy Economics and Policy, 2018)
The main goal of modern energy development all over the world is to make it accessible. Russia has large reserves of energy minerals and a significant potential for renewable energy sources. However, in Russia traditional sources of energy, for many objective and subjective reasons, are often unable to provide widespread and inexpensive electricity accessibility. In this regard, the importance of alternative energy is increasing. The article given presents an assessment of the trends in the development of renewable and alternative energy in the world. The Russian energy potential and the shaping factors have been estimated. Possibilities and experience have been considered; prospects of using alternative energy sources in the Russian regions with fundamentally different social-economic, natural-climatic and energy characteristics have been estimated. It has been proved that, despite diametrically opposite characteristics, the Russian regions have prospects and conditions for the development of alternative energy similar in many respects. Keywords: renewable energy sources, alternative energy, wind power generator, solar batteries, biogas energy JEL Classifications: Q26, Q42, R11